Association between Body Mass Index and Migraine: A Survey of Adult Population in China. (19th April 2018) - Huang, Qingqing; Liang, Xiping; Wang, Shiqiang; Mu, Xiaosong
Abstract : Both migraine and obesity are prevalent disorders in the general population, which are characterized by disability and impaired quality of life. Although so many researches had studied the association between migraine and obesity, there are still no full knowledge of the relationship between body mass index (BMI) and migraine, especially chronic migraine (CM). In this study, we analyzed a previous epidemiological survey data of primary headache patients in Chongqing, which surveyed consecutive neurological outpatients through face-to-face interview with physicians using a headache questionnaire. 166 episodic migraine (EM) patients and 134 chronic migraine (CM) patients were included in the study out of 1327 primary headache patients. And 200 healthy adults from the physical examination center were included as a control group. Finally, we found that the patients with migraine (EM and CM) were more likely to be overweight, obese, or morbidly obese compared to those in the healthy group. Significant difference was found between BMI and frequency of migraine attacks but not severity or duration of headache onset. And no significant difference was found in severity and duration of headache onset between episodic and chronic migraine among different BMI classifications. Such may update our knowledge about the clinical features of migraine and BMI, revealing that the frequency of attacks may be associated with being overweight, obese, or morbidly obese in patients with migraine and that the extent of being overweight, obese, or morbidly obese in CM patients was lower than that in EM patients.